Dinamika Islam Kultural: Studi atas Dialektika Islam dan Budaya Lokal Madura - Paisun Paisun (el Harakah: Jurnal Budaya Islam, 2010)
Throughout the history, it is well-known that the ingress and the progress of Islam in Indonesia, especially in Java and Madura, were held almost without any tension and conflict. Even in the societies with some former belief systems such as Animism and Buddhism, Islam was easily accepted as a religion that brings peace within its teachings. During periods, Islam and local cultures perform a dialectical relationship and give rise to local variances of Islam, such as Javanese Islam, Madurese Islam, Sasak Islam, Sundanese Islam, etc. Those variances of Islam are the result of an acculturation process between Islam with the local cultures. In other word, this process is also called as “inculturation”. These local variances of Islam, further termed as the “cultural Islam” in this paper, have become a characteristics of Indonesian Islamic societies phenomenon which are different from Middle-East’s Islamic society and European Islamic society. This paper discusses about the Madurese Islam, one of these cultural Islam’s variances. Dialectical process between Islam and the local culture of Madura in turn generates a unique Madurese Islam, which is distinctive and esoteric. In its further developments, Islam and Madurese tradition are seen as unity and inseparatable, though people can still distinguish one another. This study seeks to uncover and expose the Islamic cultural dynamics that exist and grow in Madura: how big is the change that occurred, in which part, and what factors underlie these changes. This study provides benefit in enriching our scientific study about Indonesian cultural heritage, especially about the dialectical relationship between Islam and Madurese local culture. Sepanjang sejarah, diketahui bahwa masuknya dan kemajuan Islam di Indonesia, khususnya di Jawa dan Madura, berlangsung hampir tanpa ketegangan dan konflik. Bahkan di masyarakat dengan beberapa sistem kepercayaan sebelumnya seperti Animisme dan Budhisme, Islam dengan mudah diterima sebagai agama yang membawa kedamaian dalam ajarannya. Selama periode tersebut, Islam dan budaya lokal melakukan hubungan dialektis dan menimbulkan varian Islam lokal, seperti Islam Jawa, Islam Madura, Sasak Islam, Islam Sunda, dan sebagainya. Perbedaan varian Islam tersebut adalah hasil proses akulturasi antara Islam dengan budaya lokal. Dengan kata lain, proses ini juga disebut sebagai "inkulturasi". Variasi Islam lokal ini, yang selanjutnya disebut sebagai "Islam budaya" dalam makalah ini, telah menjadi ciri khas fenomena masyarakat Islam Indonesia yang berbeda dari masyarakat Islam Timur Tengah dan masyarakat Islam Eropa. Tulisan ini membahas tentang Islam Madura, salah satu varian Islam budaya ini. Proses dialektis antara Islam dan budaya lokal Madura pada gilirannya menghasilkan Islam Madura yang unik, yang khas dan esoteris. Dalam perkembangan selanjutnya, tradisi Islam dan Madura dipandang sebagai kesatuan dan tak terpisahkan, meski orang masih bisa saling membedakan. Studi ini bertujuan untuk mengungkap dan mengekspos dinamika budaya Islam yang ada dan berkembang di Madura: seberapa besar perubahan yang terjadi, di bagian mana, dan faktor-faktor apa yang mendasari perubahan ini. Studi ini memberi manfaat dalam memperkaya kajian ilmiah kita tentang warisan budaya Indonesia, terutama tentang hubungan dialektis antara Islam dan budaya lokal Madura.